Choosing research methods : data collection for development workers - Pratt, Brian (Development guidelines,, 1992)
A practical manual to help development workers with the collection of data needed in the development field. A companion volume to "Social Survey Methods", this book considers the broader theoretical issues behind social research and explains and evaluates the different methods of collection in use.